(untitled) (Research, Society and Development, 2020)
The aim of this research is to present a socioeconomic diagnosis of the living and working conditions of recyclable waste pickers through an association in the city of Fortaleza, CE, which presents several problems in the process of inclusion of these professionals in the system. The incorporation of these environmental agents is a challenge, and is one of the great problems nowadays, due to the devaluation they suffer. The policies, programs and social actions aimed at this theme are aimed at reducing the deficit found in the system, and may highlight the National Solid Waste Policy as revolutionary in the process of inclusion of waste pickers through reverse logistics, selective collection and solidarity economy. The process of picking is for many pickers the only way to guarantee their survival and that of their families, especially of an attempt to be included in the labor market, even if it is perverse, and without labor laws. This research investigated through a questionnaire the gender, income, age, schooling level and the activities that the professionals from the process of cacao develop in the Association of the Collectors of the Jangurussu. The final data reveal precarious working conditions and that these workers are exposed to social prejudice, simply because of the type of activity they develop, due to the lack of decent working conditions, due to the lack of effective social policies and without the right to a fixed monthly income.